2011
DOI: 10.1136/jme.2010.040931
|View full text |Cite
|
Sign up to set email alerts
|

Language, foreign nationality and ethnicity in an English prison: implications for the quality of health and social research

Abstract: The failure to include and/or identify social subgroups of the population can undermine the value of research, including, in the case of the study prison, funded health research. This can compromise associated needs assessments and service delivery, particularly important in already disadvantaged populations; this may encourage and/or perpetuate a range of health inequalities. There is a pressing need to examine cultural exclusion in other health and criminal justice settings, to assess the ways in which-and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…They frequently lack information about various aspects of prison life, and as a result they almost never reach more active levels of the participation pyramid. For instance, this population is frequently excluded from research (Yildiz and Bartlett, 2011), which is one means of consulting prisoners. Surveys can be translated (for example, Brosens et al, 2015;Slotboom et al, 2011) or interpreters can support researchers while they conduct interviews (Bhui, 2004) to hear the perspective of foreign national and non-Dutch-speaking prisoners.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…They frequently lack information about various aspects of prison life, and as a result they almost never reach more active levels of the participation pyramid. For instance, this population is frequently excluded from research (Yildiz and Bartlett, 2011), which is one means of consulting prisoners. Surveys can be translated (for example, Brosens et al, 2015;Slotboom et al, 2011) or interpreters can support researchers while they conduct interviews (Bhui, 2004) to hear the perspective of foreign national and non-Dutch-speaking prisoners.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Having a large number of foreign nationals within a prison poses different challenges, including language barriers (Atabay 2009; Banks 2011). The literature review of Yildiz and Bartlett (2011) has shown that foreign national prisoners are frequently excluded from research. Despite the difficulty of involving them in the project, we took up the challenge, and with success.…”
Section: Discussionmentioning
confidence: 99%
“…This particular group may or may not have a different perception and experience of the issue at hand, be that prisoner-staff relations, health, recidivism and so on. Yet, on account of language (and other social and cultural) barriers foreign-national prisoners are often excluded altogether from research samples (Yildiz and Bartlett, 2011).…”
Section: Resultsmentioning
confidence: 99%